Purified and Recombinant Hemopexin: Protease Activity and Effect on Neutrophil Chemotaxis - Tian Lin; Jialin Liu; Feng Huang; Tjitske S R van Engelen; Sujatha R Thundivalappil; Frank E Riley; Michael Super; Alexander L Watters; Ann Smith; Nathan Brinkman; Donald E Ingber; H Shaw Warren (BMC, 2016)
Abstract Infusion of the heme-binding protein hemopexin has been proposed as a novel approach to decrease heme-induced inflammation in settings of red blood cell breakdown, but questions have been raised as to possible side effects related to protease activity and inhibition of chemotaxis. We evaluated protease activity and effects on chemotaxis of purified plasma hemopexin obtained from multiple sources as well as a novel recombinant fusion protein Fc-hemopexin. Amidolytic assay was performed to measure the protease activity of several plasma-derived hemopexin and recombinant Fc-hemopexin. Hemopexin was added to the human monocyte culture in the presence of lipopolysaccharides (LPS), and also injected into mice intravenously (i.v.) 30 min before inducing neutrophil migration via intraperitoneal (i.p.) injection of thioglycolate. Control groups received the same amount of albumin. Protease activity varied widely between hemopexins. Recombinant Fc-hemopexin bound heme, inhibited the synergy of heme with LPS on tumor necrosis factor (TNF) production from monocytes, and had minor but detectable protease activity. There was no effect of any hemopexin preparation on chemotaxis, and purified hemopexin did not alter the migration of neutrophils into the peritoneal cavity of mice. Heme and LPS synergistically induced the release of LTB4 from human monocytes, and hemopexin blocked this release, as well as chemotaxis of neutrophils in response to activated monocyte supernatants. These results suggest that hemopexin does not directly affect chemotaxis through protease activity, but may decrease heme-driven chemotaxis and secondary inflammation by attenuating the induction of chemoattractants from monocytes. This property could be beneficial in some settings to control potentially damaging inflammation induced by heme.